Pipeline upheaval buckling in liquefiable soils - Williams, E; Byrne, B; Blakeborough, A (2014)
This paper summarises research exploring the upheaval buckling of buried pipelines in saturated sand, focusing on loose and liquefiable soil conditions. This problem is relevant to offshore oil and gas pipelines. A series of plane-strain uplift tests were conducted to explore drained and partially drained pipe-soil behaviour, using a rig that simulates the jet-trenching installation method. The experimental force-displacement response was used in a numerical study to examine the effect on the global buckling response. The results of this work demonstrate that initial soil state and pore-pressure effects are critical influences on the mobilised uplift resistance; this must be better accounted for in upheaval buckling design guidance. © 2010 Taylor and Francis Group, London.